Viral nanomechanics with a virtual atomic force microscope. (5th June 2018) - Aznar, María; Roca-Bonet, Sergi; Reguera, David
Abstract: One of the most important components of a virus is the protein shell or capsid that encloses its genetic material. The main role of the capsid is to protect the viral genome against external aggressions, facilitating its safe and efficient encapsulation and delivery. As a consequence, viral capsids have developed astonishing mechanical properties that are crucial for viral function. These remarkable properties have started to be unveiled in single-virus nanoindentation experiments, and are opening the door to the use of viral-derived artificial nanocages for promising bio- and nano-technological applications. However, the interpretation of nanoindentation experiments is often difficult, requiring the support of theoretical and simulation analysis. Here we present a 'Virtual AFM' (VAFM), a Brownian Dynamics simulation of a coarse-grained model of virus aimed to mimic the standard setup of atomic force microscopy (AFM) nanoindentation experiments. Despite the heavy level of coarse-graining, these simulations provide valuable information which is not accessible in experiments. Rather than focusing on a specific virus, the VAFM will be used to analyze how the mechanical response and breaking of viruses depend on different parameters controlling the effective interactions between capsid's structural units. In particular, we will discuss the influence of adsorption, the tip radius, and the rigidity and shape of the shell on its mechanical response.